Dampak Pandemi Covid-19 Terhadap Tingkat Pelayanan Moda Transportasi Transjakarta Koridor 1 Blok M – Kota - Iwan Purwo Santoso; Soeyatwoko Soeyatwoko; Pratiwi Nova Kirani (Jurnal Syntax Transformation, 2021)
Transjakarta is a public transportation owned by the government of Jakarta which operated by PT. Transportasi Jakarta as the regional owned enterprise (BUMD). The enactment of the Public activity restriction issued by the government of Indonesia was followed by the Transjakarta management issuing a number of policies in order to minimize the spread of COVID-19. This study aims to find out the level of service in Transjakarta especially in the corridor 1 which cater people from Blok m- Kota during the implementation of the policies during the pandemic. The method used in this study is the survey method for collecting the premier and secondary data. The analysis in this study is using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The result of this study revealed that there is a daily operational decrease of Transjakarta Bus for corridor 1 Blok M-Kota by 76.47%, the decrease in the number of passenger per day is 59.72%. The overall satisfaction index is 84.68% meaning it is in the very satisfied category.